Acute VR competitive cycling exercise enhanced cortical activations and brain functional network efficiency in MA-dependent individuals. (13th July 2021) - Qi, Liping; Yin, Yue; Bu, Lingguo; Tang, Zekun; Tang, Lei; Dong, Guijun
Highlights: VR competitive cycling improved participants' cognitive performance and emotions. Activations in the DLFPC and M1 were found during Stroop tasks after exercise. VR competitive cycling enhanced participants' brain functional network efficiency. Abstract: Background: Methamphetamine (MA) dependence is associated with elevated rates cognitive impairment in MA users. The objective of the present study was to investigate the effects of virtual reality (VR) competitive cycling excise on the neurocognitive functions and on negative affectivity of MA-dependent individuals. Methods: Thirty MA-dependent individuals performed a colour-word Stroop task and underwent a profile of mood states (POMS) scale assessment both before and after a 10 min VR competitive cycling exercise. Functional near-infrared spectroscopy (fNIRS) were recorded during the pre-and post-exercise Stroop tasks and during rest. Results: After acute exercise, neural activity, along with improved Stroop performance, was enhanced significantly in the dorsolateral prefrontal cortex. Also observed during post-exercise Stroop tasks was a more efficient network architecture in the topological organization of brain networks than during the pre-exercise Stroop tasks. As for resting states before versus after exercisethe, we detected an increased functional connectivity between the prefrontal cortex and the motor cortex after exercise. Conclusions: These results suggest that an acute bout of VR competitive cycling exercise facilitates executive information processing by enhancing task-related cortical activations and brain functional network efficiency in MA-dependent individuals.